2003
DOI: 10.1007/s005950300071
|View full text |Cite
|
Sign up to set email alerts
|

A Granulomatous Liver Abscess Which Developed After a Toothpick Penetrated the Gastrointestinal Tract: Report of a Case

Abstract: An unusual case of a toothpick perforating the stomach, then penetrating the liver, and thereafter forming a liver abscess is reported. A 48-year-old woman who had ingested a toothpick 1 month earlier was admitted to our hospital because of severe epigastralgia which had progressively worsened. A laparotomy was performed because a granulomatous abscess in the liver due to this ingested foreign body was suspected. We found a granulomatous abscess in the liver due to the penetration of the toothpick through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 5 publications
0
46
0
1
Order By: Relevance
“…12,[15][16][17] All of our patients presented with nonspecific abdominal pain and normal radiographs. However, all 5 patients were subsequently found to have complicated FB ingestion secondary to fish bones.…”
Section: Discussionmentioning
confidence: 79%
“…12,[15][16][17] All of our patients presented with nonspecific abdominal pain and normal radiographs. However, all 5 patients were subsequently found to have complicated FB ingestion secondary to fish bones.…”
Section: Discussionmentioning
confidence: 79%
“…5 Furthermore, perforation or penetration by a toothpick can be asymptomatic, and causing later complications in adjacent structures, such as, fistula involving a major blood vessel, 6 constrictive pericarditis, 7 or a liver abscess. 8 However, it is difficult to diagnose toothpick ingestion because patients are usually ignorant of having swallowed a toothpick. In one study, it was found that only 12% of patients recalled swallowing a toothpick.…”
Section: Discussionmentioning
confidence: 99%
“…We were also able to find some artifacts made by metallic foreign material or contrast media. Although there has been one case of antibiotic therapy only [2], the recommended treatment is exploratory laparotomy to drain the hepatic abscess and eliminate the foreign body if a hepatic abscess secondary to a hepatic foreign body is detected [3,9,10,16]. Despite the benign evolution, the hepatic foreign body in the present case was considered a potentially risk factor for gall bladder rupture or abscess formation because of its location, and it was therefore removed as fast as possible.…”
mentioning
confidence: 91%
“…In humans, approximately 80-90% of ingested foreign bodies entering the stomach pass uneventfully through the gastrointestinal tract within a week without being discovered [3,9,13,16]. However, an ingested foreign body may cause hemorrhage, perforation or obstruction.…”
mentioning
confidence: 99%